Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2003
DOI: 10.1080/09553000310001596986
|View full text |Cite
|
Sign up to set email alerts
|

Time factor and treatment strategies in subclinical disease

Abstract: Rational biological development of treatment strategies for subclinical metastases has lagged behind such efforts with primary cancers: most adjuvant therapies for subclinical disease have been developed empirically, based on clinical observation. This paper reviews recent studies that point to rapid growth of subclinical disease. The effect of rapid growth of occult metastases and undetectable extensions of primary cancer is to increase the radiation dose necessary for their elimination if treatment duration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
1
6
0
1
Order By: Relevance
“…It has been shown that early application of PCI at a dose of about 30-35 Gy in 2-Gy fractions allows to obtain better results. This was confirmed by Auperin et al and Suwiński's group [3,27,28]. The latter presented a nearly linear dose-response relationship regarding reduction in brain metastases, demonstrated for "early" PCI in the dose range from 0 up to 35 Gy.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…It has been shown that early application of PCI at a dose of about 30-35 Gy in 2-Gy fractions allows to obtain better results. This was confirmed by Auperin et al and Suwiński's group [3,27,28]. The latter presented a nearly linear dose-response relationship regarding reduction in brain metastases, demonstrated for "early" PCI in the dose range from 0 up to 35 Gy.…”
Section: Discussionsupporting
confidence: 73%
“…The latter presented a nearly linear dose-response relationship regarding reduction in brain metastases, demonstrated for "early" PCI in the dose range from 0 up to 35 Gy. Additionally, PCI applied at the beginning of chemoradiotherapy reduces the incidence of brain metastases by about 80% [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…One possibility is that dose less that 95% of prescription dose is adequate to treat clinically negative axilla/microscopic disease. Wither et al have proposed a shallow dose response curve for microscopic disease though a dose of 45 Gy to 50 Gy seems more relevant for sterilization of subclinical disease [28]. It is possible that a dose in order of 30 Gy can bring about some regional control.…”
Section: Discussionmentioning
confidence: 99%
“…Following the radiobiological concepts of Withers et al [21] a dose of 50 Gy in 2 Gy per fraction is considered as necessary to achieve an overall 90% reduction in the incidence of metastases and it is a commonly prescribed dose-schedule for subclinical disease. On the other hand, there are also suggestions from the literature that worthwhile benefits can be achieved by doses as low as 14Á21 Gy under the condition of being delivered close to the treatment of the primary [22,23]. We did not make any attempt on the biological dose calculation though different dose per fraction and treatment times were used.…”
Section: Discussionmentioning
confidence: 99%